Remoção de flúor utilizando adsorventes comerciais e um novo material sintetizado à base de grafeno - Marin, Pricila (2017)
In order to contribute to treatment of water contaminated with excess fluoride ions, the aim of this study is to evaluate the fluoride removal by adsorption process in batch system and in fixed bed column. Two commercial materials (Activated Alumina, AAD, and DowexTM Marathon A resin, RMA) and another synthesized based on graphene were used. Firstly, reduced graphene oxide was synthesized, functionalized with ZrCl4 particles and supported on activated carbon of vegetable origin, resulting in the G-ZrCl4/CAV composite. The material was characterized using scanning (SEM) and transmission (TEM) electron microscopy, N2 physisorption by BET and BJH methods, X-ray diffraction (XRD), Fourier transformed infrared spectroscopy (FT-IR), energy dispersive X-ray spectrometry (EDX) and Raman spectroscopy. Fluoride removal in batch system was evaluated under different conditions of pH (2 - 12), agitation (70, 100, 130 and 160 rpm) and temperature (20, 30, 40 and 50 °C). In a fixed bed system, the breakthrough curves were obtained at different conditions of solution concentration and feed flow rate. The results of G-ZrCl4/CAV characterization prove that the material synthesized has favorable properties for use as an adsorbent of fluoride ions. The batch adsorption tests indicate that among the evaluated conditions, all materials presented the best results at pH 2, agitation of 130 rpm and 30 °C of temperature. The equilibrium of the system was reached in 5 hours for G-ZrCl4/CAV and 4 hours for AAD and RMA. The pseudo-first order kinetic model was the one that best described the kinetic data of G-ZrCl4/CAV, while for AAD and RMA, the kinetic data were better described by pseudo-second order model. The Langmuir isotherm was the one that best represented the equilibrium experimental data, presenting maximum adsorption capacities of 3.90 mg g-1, 1.57 mg g-1 and 26.83 mg g-1 for G-ZrCl4/CAV, AAD and RMA, respectively. The thermodynamic study indicated that the process occurs spontaneously for the three materials and suggests that the fluoride adsorption by G-ZrCl4/CAV, AAD and RMA is an exothermic process. In the fixed bed system, among the conditions evaluated, it was observed that the best results were obtained when working with the more concentrated fluoride solutions and the higher flow rates. The adsorption capacities achieved in fixed bed were considerably higher than those obtained in the batch process with values equal to 41.80 mg g-1, 21.63 mg g-1 e 53.38 mg g-1 for G-ZrCl4/CAV, AAD and RMA, respectively. These results indicate that RMA has the highest fluoride removal capacity both in batch and in fixed bed columns. Based on the results obtained for the two types of process, the materials presented excellent fluorine adsorption capacities when compared to other adsorbents available in the literature, thus demonstrating the feasibility of using these materials in the fluoride removal for treatment of water intended for human consumption.